A descriptive Analysis of Anglicism used in Ecuadorian Newspapers - Loaiza Massuh, Eva María de Lourdes (2012)
Have you noticed that in our country, Ecuador, the use of Anglicisms in newspapers, is getting more and more frequent? That is why this investigation is titled: A Descriptive Analysis of Anglicisms Used in Ecuadorian Newspapers. Throughout this investigation study, which was developed in Guayaquil, the following three facts will be noticed: first, the modification in language usage in newspapers related with the expressions where Anglicims are used. Second, the social factors for language variation in Ecuador, remarking the influence of the English language. Third, that many times it is unnecessary to use words and phrases borrowed from other languages. The variables used for this investigation were: a national newspaper ―Diario El Universo‖, a local newspaper ―Diario Expreso‖, and a tabloid, ―El Extra‖. The subvariables used for this investigation were the following newspapers´ sections: news, advertisements, social pages, reports, and sports.